Peripartum optimization and coordination of collaborative care practice: a critical role for the obstetric anesthesiologist in combating maternal morbidity and mortality. Issue 3 (June 2021) - Gitterman, Anna; Klaus, Joseph; Williams, Kayode; Murphy, Jamie
Abstract : Purpose of review: Antenatal anesthesia clinics remain uncommon despite the rising incidence of maternal morbidity and mortality in the United States. The purpose of the present review is to outline the major considerations and challenges surrounding antenatal anesthetic evaluation. Recent findings: Data from the general surgical population would suggest a mortality benefit associated with preoperative anesthesia evaluation, although no such data exists in the obstetric population. Robust systems for case ascertainment and referral are needed. Recent publications on obstetric comorbidity indices may provide useful tools to ascertain high-risk parturients for a referral to antenatal obstetric anesthesiology clinics and higher levels of maternal care. Major obstetric organizations have identified and laid out criteria for maternal level of care. Anesthesiology resources also play a role in these designations and can help triage patients to facilities with appropriate resources. Summary: Obstetric anesthesiologists have a critical role not only in preoperative patient optimization but also in coordinating multidisciplinary care for optimal patient outcomes.